Determinants of CD4 Cell Count among Antiretroviral Therapy (ART) Attendant HIV Positive Adults Using Longitudinal Data Analysis in University of Gondar Referral Hospital - Koyachew Yenaneh Tadege; Tigist Jegnaw; Kasim Mohammed Yesuf (Asian Journal of Medical Research, 2019)
Background: CD4 count is the best predictor for disease status and immediate risk of death and thus should be used to identify those who have advanced HIV disease. The aim of this study to investigating the basic factors of CD4cell count and assessing the progression of CD4cell count among HIV positive adults those they were attending university of Gondar Referral ART clinic, since December 2012 up to December 2017.Subjects and Methods:Since, the outcome variable was measured repeatedly through time and measurements within the patient were correlated. Such type of data requires a special types of modeling strategy, there for longitudinal data analysis plays a major role on such type of data analysis. Linear mixed model with unstructured correlation matrix were used to model the data in this study by including fixed and random factors on the model.Results:From the total of 216 Study subjects were followed retrospectively 61.08% and 38.92 were females and males respectively. The maximum number of observation per subject was 10 and the minimum and maximum CD4cell counts were 65 and 1440 respectively.Conclusion: Based on the findings of the study religion (orthodox, and Muslim), weight, baseline CD4cell count, time, TB screen positive, hemoglobin level, regimen type (d4t-3TC-NVP and AZT-3TC-NVP)and the interaction effect of time with baseline CD4count was significant predictors of CD4count. We would like to recommend for the patients must be, punctual, initiated to ART with high base line CD4count and hemoglobin level.